Mengukur Pengaruh Kehadiran pada Pembelajaran Daring Tatap Maya Terhadap Capaian Kompetensi Kognisi Peserta Didik Kelas XII SMA Negeri 1 Sungailiat Kabupaten Bangka - Suhendra Suhendra (JURNAL PENDIDIKAN ROKANIA, 2021)
The purpose of this research is to find information related to (1) the categogy of casual connection between students’ presence in online virtual learning process to cognitive competence achievement. (2) the greatness of students’ presence effect in online virtual learning process to cognitive competence achievement. This is evaluation research with quantitative approach. The datas used in this research are primer data which is cognitive competence achievement collected by test, the presence degree found through observation and the degree of serving satisfaction got by question. Statistical test used in research is simple regression analysis. On the 5 % significant phase, it can be concluded that (1) the students’ presence in the online virtual learning process has low category of casual connection to cognitive competence achievement, (2) the effect of students’ presence in the online virtual learning process to cognitive competence achievement is 4,47%.